Influence of Macroeconomics Factors, Profitability, and Stock Trading Volume on Stock Prices in The Years 2019-2021 - Anisa Fitriani; Febryanti Simon (Pandawan, 2024)
The Covid-19 pandemic, which struck Indonesia in March 2020, impacted various sectors, including the capital market. The capital market, which primarily served as a source of funding for investors, was also affected. This research was designed to examine the impact of economic elements on the share prices of manufacturing sectors amidst the Covid-19. The aspects under examination encompassed exchange rate, inflation, probability, and stock trading volume. This research employed data from all total of 171 manufacturing industry firms listed on the Indonesia Stock Exchange (IDX) over the period from 2019 to 2021 . The research method used is a quantitative method. The total sampling technique used resulted in a sample of 59 (fifty-nine) companies that met the research criteria. The method of data analysis employed is panel data regression analysis, utilizing the Random Effect Model (REM) estimation, which is tested using Eviews 12. The findings indicate that profitability significantly influences stock prices, while exchange rate, inflation and stock trading volume do not have a significant effect on the stock prices of manufacturing companies during 2019-2021. Based on the simultaneous test result obtained, exchange rate, inflation, profitability, and stock trading volume have a significant effect on stock prices.